Analisis Pengaruh Utilitarian, Hedonic, Privacy, Trust Terhadap Attitude Toward Online Purchasing, Dan Pengaruh Attitude Toward Online Purchasing Terhadap Purchase Intention Pada Generasi Milenial - Wisnu Yuwono; Julyati Julyati (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The millennial generation has an important role in the development of online purchasing because it grows at a time when technology has advanced, especially through the use of smartphone applications. This study aims to analyze the effect of utilitarian, hedonic, privacy, andtrust on attitude toward online purchasing, and attitude toward online purchasing on online purchase intention. The research method used is a quantitative approach by distributing questionnaires to the millennial generation in Batam City. Through the SmartPLS application tool, the results show that utilitarian and hedonic have a significant positive effect on attitudes toward online purchasing, while privacy and trust have no significant effect on attitudes toward online purchasing. In addition, attitude toward online purchasing has a significant positive effect on online purchase intention. The results of this study provide recommendations to companies in strategies to increase online sales among millennials